Development of a method for the monitoring of odor‐causing compounds in atmospheres surrounding wastewater treatment plants. Issue 9 (10th May 2013) - Godayol, Anna; Marcé, Rosa M.; Borrull, Francesc; Anticó, Enriqueta; Sanchez, Juan M.
<x xml:space="preserve">Abstract</x> This study describes the development of an analytical method based on active collection in a multisorbent Tenax TA/Carbograph 1TD tube, followed by thermal desorption and GC‐MS for the determination of 16 volatile organic compounds in air samples. The analyzed compounds include ozone precursors and odor‐causing compounds belonging to different chemical families (sulfur‐ and nitrogen‐containing compounds, aldehydes, and terpenes). Two types of sorbents were tested and desorption conditions (temperature, time, and sampling, and desorption flow) were evaluated. External calibration was carried out using the multisorbent bed. Method detection limits in the range 0.2–2.0 μg m−3 for 1 L samples were obtained. The method was applied for determining the target compounds in air samples from two different wastewater treatment plants. Most compounds were detected and toluene, limonene, and nonanal were found in particularly high concentrations with maximum values of 438, 233, and 382 μg m−3, respectively.